2004
DOI: 10.1021/ol0485518
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of β-Amino Acids Based on Oxidative Cleavage of Dihydropyridone Derivatives

Abstract: [reaction: see text] A new method for the synthesis of beta-amino acids based on 2,3-dihydropyridones as starting materials is presented. Conversions of 2,3-dihydropyridones with NaIO4 and subsequently with base gave the corresponding beta-amino acids in a one-pot procedure. The reactions have been monitored by 1H NMR indicating that the beta-amino acids were formed in quantitative yields mostly. This method appears to be of broad scope, as 2-substituted 2,3-dihydropyridones are easily accessible via N-acylimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…13 Construction of Site-Directed Mutants of PAM. TcPAM point mutants were generated using the QuikChange II sitedirected mutagenesis kit (Stratagene, La Jolla, CA) and Turbo Pfu polymerase (Stratagene, La Jolla, CA) along with the respective oligonucleotide primers: Y80F-For-(5 0 -AGACGGT GCTGATATCTTTGGCGTTACCACGGGTTTCGG-3 0 ) and L104A-For-(5 0 -GCAGGAGAGCGCCATCCGCTGTC-3 0 ).…”
mentioning
confidence: 99%
“…13 Construction of Site-Directed Mutants of PAM. TcPAM point mutants were generated using the QuikChange II sitedirected mutagenesis kit (Stratagene, La Jolla, CA) and Turbo Pfu polymerase (Stratagene, La Jolla, CA) along with the respective oligonucleotide primers: Y80F-For-(5 0 -AGACGGT GCTGATATCTTTGGCGTTACCACGGGTTTCGG-3 0 ) and L104A-For-(5 0 -GCAGGAGAGCGCCATCCGCTGTC-3 0 ).…”
mentioning
confidence: 99%
“…Many approaches to their synthesis have been developed [16][17][18][19][20][21]. Oxohydropyridines can also be used as precursors in the stereoselective synthesis of substituted [22] or disubstituted b-amino acids [23].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the low solubility of salts such as 1 can lead to variable results and has hampered attempts to scale up the reduction.Recently, it has been demonstrated that similar unsubstituted dihydropyridones are accessible Via nucleophilic addition to 4-methoxy substituted pyridinium salts. [3][4][5][6] Encouraged by these results, we proposed that addition of Grignard reagents to pyridinium salts such as 1, followed by acidic…”
mentioning
confidence: 99%
“…Recently, it has been demonstrated that similar unsubstituted dihydropyridones are accessible via nucleophilic addition to 4-methoxy substituted pyridinium salts. Encouraged by these results, we proposed that addition of Grignard reagents to pyridinium salts such as 1 , followed by acidic hydrolysis, could provide a useful alternative to the Birch reduction, but this time using the aromatic heterocycle as an electrophile.…”
mentioning
confidence: 99%